2020
DOI: 10.1109/mcg.2020.2973120
|View full text |Cite
|
Sign up to set email alerts
|

Nano for the Public: An Exploranation Perspective

Abstract: Public understanding of contemporary scientific issues is critical for the future of society. Public spaces, such as science centers, can impact the communication of science by providing active knowledge-building experiences of scientific phenomena. In contributing to this vision, we have previously developed an interactive visualization as part of a public exhibition about nano. We reflect on how the immersive design and features of the exhibit contribute as a tool for science communication in light of the em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Their work has found successful applications, e. g., in astronomy dissemination [6]. Such applications can often be deployed as museum or science center exhibits [23], [40] and facilitate broad audience learning.…”
Section: Visualization For Science Outreachmentioning
confidence: 99%
“…Their work has found successful applications, e. g., in astronomy dissemination [6]. Such applications can often be deployed as museum or science center exhibits [23], [40] and facilitate broad audience learning.…”
Section: Visualization For Science Outreachmentioning
confidence: 99%
“…The focus of attention of various scholars, such as Jones et al (2013), in the STEAM interdisciplinary educational approach, leads to discussions related to the integration of NST in Primary school curricula. NST is a new scientific field of research and development that has shown rapid development worldwide over the last two decades Höst et al, 2020). NST is not a distinct, independent scientific object.…”
Section: Nst As the Pre-eminent Interdisciplinary Field Of Knowledgementioning
confidence: 99%